Use of Eucalyptus Charcoal Waste in the Formulation of Substrate for the Cultivation of Two Strains (LED 20/11 and LED 20/12) of Lentinula edodes - Zied, Diego Cunha [UNESP]; Silva, Bianca Domingues [UNESP]; Caitano, Cinthia Elen Cardoso [UNESP]; Vieira Junior, Wagner Gonçalves [UNESP]; da Silva Freitas, Marcos Antônio [UNESP]; Teixeira, Pedro Afonso Gomes [UNESP]; Pardo-Giménez, Arturo (MDPI, 2024)
The shiitake mushroom (Lentinula edodes) is globally valued for its nutrition and medicinal properties. New technologies aim to increase production with less environmental impact, considering materials such as charcoal for substrate enrichment. This manuscript evaluated the effect of fine charcoal (FC) on the substrate formulation of two L. edodes strains (LED 20/11 and LED 20/12). The substrate consisted of 72% eucalyptus sawdust, 12.5% rice bran, 12.5% wheat bran, and 3% calcium carbonate (control treatment without charcoal). Treatments with FC proportionally reduced the use of sawdust, with doses of 1%, 2%, 4%, 8%, and 16% (relative to the substrate material). Yield, mushroom number, and mushroom weight were evaluated. The concentration of FC significantly affected the parameters analyzed, especially at the 4% dose. A negative correlation between mushroom number and weight was observed. For yield, the control treatment and the lowest dose of FC (1%) had the highest yields for the first harvest. Strain LED 20/12 showed lower yield variability due to the percentage of FC applied to the substrate. The incorporation of FC into the substrate for shiitake cultivation demonstrates efficacy; however, both the concentration and strain used are limiting factors for its applicability.
Keywords: quality screening of mushroom; shiitake; strains; substrate formulation; yield